A Representação social do corpo no ritual de promessa no catolicismo da cidade do Recife. - Oliveira, Ilka Maria da Silva (2017)
This dissertation discusses the social representation of the body in the promise rituals in the catholicism, characterized by the pluralism of the manifestations, present in the cultural and religious experience, resulting from the construction of meanings of the devotee relationship with the sacred. The participant's universe was defined in the three great religious celebrations, that happens in the urban perimeter of the city of Recife/PE and where concentrates a great number of followers, which were chosen in a random way and that they accepted to answer an interview of open questions, in order to bring the interviewees, to think and to talk about the importance of the body for the accomplishment of his promise ritual. This study is based in the Theory of the Social Representations and their theoretical of reference, for now, we apprehended the symbolic universe of speaking and of acting, classifying the social representations that go beyond the execution of the promise, through the speech of the devotee , explaining on the mechanisms that are used to understand the need to express with the body the devotion. Located in the field of the Sciences of the Religion, It has the intention of getting to do present an idea, through an object, which not always it is conscious for the individual. By the approach with the phenomenon of the payment of the promise, we noticed how they live their practices devocionais, as they aim at and they anchor them and how that contributes for the conservation of the 'habitus' in the Brazilian religious field. In the conclusion phase, we analyzed the explicit behaviors, linked by an intentional causal relationship, centered in the totality of the speech, with few generic subjects that represent the group. We built nested and systematized arguments established starting from the consensus interpretations and of the critic of the creative contradiction. We will present the transposition of the data, punctuating the relationships between the social representations and the symbolic elements that were mapped, as characteristic result of the research.